Investigation of Wire Diameter of Helical Compression Spring for Payload Separation - Laksono, Shandi Prio (BRIN Publishing, 2021)
The payload is designed to be separated from rocket at an altitude over 100 km. Â One of critical component in the payload separation system is the helical compression spring. The helical compression spring ensures safe release the payload. The spring must satisfy some parameters such as static failure and buckling, also spring has enough energy storing to release the payload during launch. The objective of this paper is to do investigation of wire diameter of helical compression spring which can be used in the payload separation system of sounding rocket based on several constraints. The results obtained show that with payload weight of 60 kg, minimum wire diameter should be 8 mm with mean coil diameter of 80 mm. The maximum separation velocity of 1.76 m/swas obtained by using wire diameter of 8 mm and mean coil diameter of 96 mm.